VD_FINDINFO Décision / 2018 / 1074 vom 11. Dezember 2018 - VD Tribunal cantonal (2018)
PLAIGNANT, PARTIE CIVILE, PLAINTE PÉNALE, ADMISSION DE LA DEMANDE | 30 al. 1 CP, 30 al. 5 CP, 118 al. 1 CPP (CH), 119 CPP (CH)